The Moore-Penrose inverse of differences and products of projectors in a ring with involution - Zhu, Huihui (2016)
In this paper, we study the Moore–Penrose inverses of differences and products of projectors in a ring with involution. Some necessary and sufficient conditions for the existence of the Moore–Penrose inverse are given. Moreover, the expressions of the Moore–Penrose inverses of differences and products of projectors are presented.